Visual Representation of Election News Reporting on Kompas.id Infographics: A Social Semiotic Analysis Based on Kress and Van Leeuwen - Kharina Putri Rosdiana; Nuryah Asri Sjafirah; Achmad Abdul Basith (Indonesian Journal Publisher, 2026)
The use of news visualization through infographics in online media has become increasingly important in simplifying the complexity of political data related to general elections. This study aims to analyze the representation of messages, interactions, and visual composition in the infographic series of the 2024 Election published by Kompas.id. This research employs a descriptive qualitative method within a constructivist paradigm using the Social Semiotics approach developed by Gunther Kress and Theo Van Leeuwen. The data consist of five infographics from the 2024 Election series published on Kompas.id and were collected through documentation studies and visual observation. The results and discussion show that Kompas.id applies mixed visual strategies in presenting election information. In the conceptual metafunction, the identity of political officials is constructed in a formal and authoritative manner through an inclusive analytical structure and the equal positioning of political actors with audiences through covert taxonomy. In the narrative metafunction, fluctuations in line graphs are interpreted as storylines that illustrate electoral dynamics, while human contexts are represented through participants’ real actions. In the dimensions of interaction and composition, Kompas.id predominantly employs the offer viewpoint and open framing to create an objective impression of election data. This study contributes to the field of visual communication and digital journalism by demonstrating that infographic-based election reporting can transform abstract political data into informative and educational constructions of political reality.